Republic of Belarus: Financial sector review and private sector financing - Luca Gattini; Sofia Borysko (European Investment Bank (EIB), 2018)
The study assesses the macro-financial situation of Belarus. It analyses the Belarus financial sector, with a specific look at the banking sector. Moreover this study explores the private sector financing environment. In particular the study investigates the SMEs segment and looks at the needs of the intermediaries that specialize in SME financing. It examines the needs and obstacles of SMEs in getting financing, including their access to finance conditions as well as the institutional environment. – – In dieser Studie wird die gesamtwirtschaftliche Lage in Belarus behandelt. Der belarussische Finanzsektor wird analysiert, und ein besonderer Schwerpunkt liegt auf dem Bankensektor. Außerdem untersucht die Studie das für den Privatsektor geltende finanzielle Umfeld. Vor allem geht die Studie auf das KMU-Segment ein und prüft den Bedarf von Partnerinstituten, die sich auf KMU-Finanzierungen spezialisieren. Sie enthält eine Bestandaufnahme des Bedarfs von KMU. Außerdem werden die Schwierigkeiten aufgelistet, mit denen KMU beim Zugang zu Finanzierungen konfrontiert sind. Dazu gehören auch die ihnen gebotenen Finanzierungskonditionen und die institutionellen Rahmenbedingungen.
Keywords: 330; banking; Belarus; financial market; financial policy; macroeconomics; private sector; small and medium-sized enterprises; Finanzsektor; Bank; Finanzmarkt; Mikrofinanzierung; Unternehmensfinanzierung; KMU; Weißrussland